Bladder incarceration within a displaced pelvic ring nonunion. (June 2021) - Taylor, Aaron; Lipof, Jason; Soin, Sandeep
Abstract: Pelvic ring injuries can be challenging to manage and may have a range of associated injuries. When bladder injuries occur in combination with pelvic ring fractures, a multidisciplinary approach may be required to plan the best course of treatment. Acute entrapment or injury to the urinary bladder after a pelvic fracture is well reported. Here, we present an interesting case of chronic bladder incarceration within a lateral compression pelvic ring injury nonunion after failed nonoperative management of the initial pelvis fracture. Treatment of the nonunion was complicated by an incidental diagnosis of lymphoma.